The characteristics and influencing factors of change in farmland system vulnerability: A case study of Sanmenxia City, China - Niu, Pu; Jiang, Yulong; Yang, Yongfang; Wang, Li (Frontiers in Environmental Science, 2022)
Farmland socio-ecological system is an integral part of regional ecological system, which provides the evolution of the whole ecosystem vulnerability from an important aspect. Based on the theory of ecosystem vulnerability, the VSD assessment framework and index system of farmland system vulnerability were constructed by using multi-factor comprehensive analysis, ArcGIS spatial analysis and factor contribution model. We evaluate the dynamic changes and influencing factors of farmland system vulnerability in Sanmenxia City, aiming to demonstrate the rules for change of the farmland system vulnerability. The results showed that the vulnerability of the farmland system in Sanmenxia City showed a downward trend in 17 years, from 0.60 in 2000 to 0.36; From a spatial perspective, the distribution of farmland system vulnerability is uneven in each district and county. The vulnerability pattern changed from "high in the Middle East-low in the southwest" in 2000 to "high in the Middle East-low in the southeast" in 2016. Population growth, high-speed urbanization, farmland use intensity and factor input intensity and other human social and economic activities and the implementation of regional agricultural policies have reduced the natural risk impact on the farmland social-ecological system to a certain extent. It is of great significance for revealing the overall evolution process and mechanism of regional ecosystem to discuss the law of farmland social-ecosystem vulnerability in typical areas.